Emission reduction technique on existing diesel engines using renewable fuels. Issue 1 (31st December 2022) - Vijayanand, G.; Augustine, Anbarasu; Ananda Natarajan, V.; Srinivasa Raman, V.; Mohanavel, Vinayagam; Christopher, D.
Abstract : In this study, the impact of blending alcohol (cyclo-octanol) with palm biodiesel on its emission patterns is carried out in a constant diesel engine. The study is intended to lessen the CO, HC, NOX and Smoke emissions when fuelled with neat palm biodiesel and the alcohol blends. Palm biodiesel is processed via transesterification from raw palm oil. Alcohol having a purity of 98.2% is employed in this study. Neat palm biodiesel (BD100), alcohol mixed with palm biodiesel on 10% volume basis (A10BD90), and alcohol mixed with palm biodiesel on 20% volume basis (A20BD80). No base and modified fuels require any slight modifications while combusted in the engine. It was noticed that by adding 10 and 20% of alcohol to palm biodiesel resulted in a significant reduction in HC, CO, Smoke and NOX emissions. Hence, the addition of alcohol helped to improve the emission characteristics of palm biodiesel.